Water diffusion measurements in cement paste, mortar and concrete using a fast NMR based technique. (30th October 2020) - Fleury, M.; Chevalier, T.; Berthe, G.; Dridi, W.; Adadji, M.
Graphical abstract: Highlights: 3-year measurement program to obtain pore diffusion coefficients on 30 samples. A NMR based fast diffusion measurement technique is used. Pore diffusion were determined on cement pastes, mortar and concrete, including fibers. two types of cement are considered (CEM I and CEMV) Abstract: With a NMR based fast diffusion measurement technique we performed a comprehensive experimental program on 30 samples to measure the pore diffusion coefficient in two series of cement pastes, mortar and concrete made with an ordinary Portland cement (CEM I) and a composite cement (CEM V). In addition, measurements were also possible in the presence of fibers and their effect could be evaluated. The principle is to monitor a deuterium-water exchange in a well-defined cylindrical geometry. The NMR technique allows the measurement of 1 H concentration inside the sample as a function of time, while ignoring 1 H outside the sample. Using well known analytical formulations, the diffusion curve can be fitted to obtain the pore diffusion coefficient of the material. The results are first presented in terms of the measured pore diffusion coefficients at 30 °C characterizing the porous network independently of porosity. For CEM I based materials, the measured values are Dp  = 7.6 ± 1.4x10 −12 m 2 /s for pastes, 40 ± 20x10 −12 m 2 /s for pastes with fibers, 9.5 ± 0.6x10 −12 m 2 /s for mortars, 4.4 ± 0.2x10 −12 m 2 /s for concretes and 28 ± 7x10 −12 m 2 /s for concretes with fibers. For CEM V based materials, the measured values are Dp  = 1.1 ± 0.4x10 −12 m 2 /s for pastes, 9.3 ± 2.7x10 −12 m 2 /s for pastes with fibers, 0.8 ± 0.1x10 −12 m 2 /s for mortars, 5.9 ± 2.2x10 −12 m 2 /s for concretes and 5.3 ± 0.8x10 −12 m 2 /s for concretes with fibers. In all cases, the fibers produce an increase of Dp together with a sample dependent result within a set of 3. When expressed in terms of effective diffusion by taking into account the porosity that can be exchanged by D2 O estimated during the diffusion experiments, the results were found in agreement with a few existing values measured with HTO through diffusion techniques (Dp  = 2.1 ± 0.4×10 −12 m 2 /s for the CEMI paste, 1.1 ± 0.06×10 −12 m 2 /s for the CEMI mortar, 0.12 ± 0.02×10 −12 m 2 /s for the CEMV concrete with fibers).